2022
DOI: 10.1002/clt2.12187
|View full text |Cite
|
Sign up to set email alerts
|

The health economic impact of cow's milk allergy in childhood: A retrospective cohort study

Abstract: Background: Cow's milk allergy (CMA) is one of the most common food allergies among children. Whilst avoidance of cow's milk protein is the cornerstone of management, further treatment of symptoms including those affecting the gastrointestinal, skin and respiratory systems plus other allergic comorbidities, maybe required. This study aimed to quantify the wider economic impact of CMA and its management in the United Kingdom (UK). Methods:We conducted a retrospective matched cohort study on children with CMA (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…A cost‐effectiveness analysis of the two models was beyond the scope of this project but would be valuable to understand the costs of delivering the services, any cost savings and improvements in outcomes for patients. A recent paper, however, has described the increased health economic impact of CMA in childhood, 41 for which our findings may provide some solutions. One obvious difference between the models is the availability of group sessions in dietetic community care, which could result in some cost savings assuming most patients do not subsequently require individual support.…”
Section: Discussionmentioning
confidence: 70%
“…A cost‐effectiveness analysis of the two models was beyond the scope of this project but would be valuable to understand the costs of delivering the services, any cost savings and improvements in outcomes for patients. A recent paper, however, has described the increased health economic impact of CMA in childhood, 41 for which our findings may provide some solutions. One obvious difference between the models is the availability of group sessions in dietetic community care, which could result in some cost savings assuming most patients do not subsequently require individual support.…”
Section: Discussionmentioning
confidence: 70%
“…Results from the current review suggest that food allergy accounts for a relatively modest proportion of the total healthcare spending of western countries but is a significant cost contributor nevertheless [3 ▪ ,8,10 ▪ ,13]. Much of the cost of food allergy stems from routine allergy care, but a sizeable proportion can also be attributed to emergency room visits and hospitalizations [3 ▪ ,8,12 ▪ ,13].…”
Section: Discussionmentioning
confidence: 86%
“…European and American studies have demonstrated, however, that individuals with food allergy incur greater direct healthcare costs relative to comparison groups constituted of both individuals without a food allergy and those without a specific allergy of interest (e.g. peanut allergy) [10 ▪ ,11,12 ▪ ,13,14]. Similar to the total direct costs, estimates of the additional or incremental healthcare costs incurred by individuals with food allergy vary across studies, ranging from +$465.06 per person per year (i.e.…”
Section: Healthcare System Costsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the patient is most often referred to a hospital dietician or an allergy clinic [ 10 ]. Cow’s milk allergy management has an economic impact that generates an increase in health costs due to the duplication in medical consultation between the PCP, the hospital [ 12 ], and the other health services, such as specialized nutrition [ 13 ]. Several studies have highlighted the clinical [ 14 ], population-level [ 15 ], and economic burden of cow’s milk allergy [ 11 ].…”
Section: Introductionmentioning
confidence: 99%